Sublime in Cinema - Freeland, Cynthia A. (Iluminace, 2002)
Characteristics of the concept of sublimity in film and its basic features. Sublimity from a philosophical point of view. The influence of sublimity in film on the perception of the audience and their emotional experience. Examples of reflexivity of emotions when watching specific titles or film scenes.
Keywords: philosophy and film; film aesthetics; perception; aesthetics in film